2017
DOI: 10.4172/2157-7579.1000477
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Prevalence of GIT Nematodes on Bovine in and aroundKombolcha and Dessie Town, North Eastern, Ethiopia

Abstract: A cross sectional study was carried out from November 2014 to April 2015 to determine the prevalence of bovine gastrointestinal tract (GIT) nematodes and associated risk factors by using flotation technique and fecal culture in and around Kombolcha and Dessie town. Out of 384 bovines examined for GIT nematodes, 160 (41.7%) animals were found positive for single or mixed GI nematode infection. The findings of fecal examination revealed eggs of Strongyle, Ascaris and Trichuris type were identified. Cattle harbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
4
1
1
Order By: Relevance
“…Finally, our results for Strongyloides spp. are in line with some studies [13,32,34,36], while other studies did not find this parasite [5,10,12,[37][38][39].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Finally, our results for Strongyloides spp. are in line with some studies [13,32,34,36], while other studies did not find this parasite [5,10,12,[37][38][39].…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence values of the gastrointestinal parasites recorded in the present study are, on the whole, in line with most of the studies conducted in Ethiopia [3,5,[10][11][12][13]15,[32][33][34][35][36][37][38][39][40]. In some studies, gastrointestinal nematodes (GIN) were considered all together, including GIS, Strongyloides spp., ascarids and trichurids, and the overall prevalence was, therefore, exceeding the prevalence of GIS alone [5,13,36,39].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Comparatively, this study documented lower prevalence than the reports of Alemu et al [ 13 ], Abera et al [ 26 ], and Fesseha and Mathewos [ 27 ] who reported overall prevalence of lungworm infection in small ruminants: 53.60%, 57.6%, and 44.02%, in Asella province, in Bale and Arsi zones, and in Durame District, southern Ethiopia, respectively. The results of this study, on the other hand, showed a relatively higher prevalence compared to reports of Asaye and Alemneh [ 28 ] (22.71% in Bahir Dar City, Amhara Region, Ethiopia) and Borji et al [ 10 ] (10.85% in Mashhad of northeast Iran). The climate, altitude, intermediate hosts, favorable ecological conditions, the sheep and goat management systems of the respective study areas for the development of lungworm species, differences in the sample sizes used during the various investigations, seasonal variation during the investigation period, variation in the nutritional status of the small ruminants, and other factors may all contribute to the variation in the overall prevalence of lungworm infections in small ruminants across the study sites.…”
Section: Discussioncontrasting
confidence: 79%